FcγR interaction is not required for effective anti‐PD‐L1 immunotherapy but can add additional benefit depending on the tumor model. Issue 2 (12th November 2018) - Sow, Heng Sheng; Benonisson, Hreinn; Breukel, Cor; Visser, Remco; Verhagen, Onno J.H.M.; Bentlage, Arthur E.H.; Brouwers, Conny; Claassens, Jill W.C.; Linssen, Margot M.; Camps, Marcel; van Hall, Thorbald; Ossendorp, Ferry; et al.
Abstract : Immunomodulatory antibodies blocking interactions of coinhibitory receptors to their ligands such as CTLA‐4, PD1 and PD‐L1 on immune cells have shown impressive therapeutic efficacy in clinical studies. The therapeutic effect of these antibodies is mainly mediated by reactivating antitumor T cell immune responses. Detailed analysis of anti‐CTLA4 antibody therapy revealed that an optimal therapeutic efficacy also requires binding to Fc receptors for IgG, FcγR, mediating depletion of intratumoral regulatory T cells. Here, we investigated the role of Fc binding in anti‐PD‐L1 antibody therapy in the MC38 C57BL/6 and CT26 BALB/c colon adenocarcinoma tumor models. In the MC38 tumor model, all IgG subclasses anti‐PD‐L1 showed similar therapeutic efficacy when compared to each other in either wild‐type mice or in mice deficient for all FcγR. In contrast, in the CT26 tumor model, anti‐PD‐L1 mIgG2a, the IgG subclass with the highest affinity for activating FcγR, showed stronger therapeutic efficacy than other IgG subclasses. This was associated with a reduction of a myeloid cell subset with high expression of PD‐L1 in the tumor microenvironment. This subclass preference for mIgG2a was lost in C57BL/6 × BALB/c F1 mice, indicating that the genetic background of the host may determine the additional clinical benefit of the high affinity antibody subclasses. Based on these data, we conclude that FcγR are not crucial for anti‐PD‐L1 antibody therapy but might play a role in some tumor models. Abstract : What's new? Monoclonal antibodies against T cell "exhaustion"‐inducing molecules show striking success in reactivating the antitumor immune response, but it is unclear if this success involves the so‐called Fc region of the antibody that activates the immune system. Here the authors systematically swapped constant regions of a known mouse antibody against programmed death‐ligand‐1 (PD‐L1) to alter interactions with the Fc receptor. The outcome was nuanced with different results obtained in different mouse tumor models leading the authors to conclude that in some tumors anti‐PD‐L1 immunotherapies might be enhanced with proper Fc receptor interactions.